Oxidation of Glycolic Acid by N-Bromosaccharin: A Kinetic and Mechanistic Study in Presence and Absence of Cationic Surfactant - Gupta, M.K.; Lagarkha, Rekha; Sharma, P.K.; Sharma, K.; Sharma, V.K. (Asian Journal of Chemistry, 2010)
The oxidation of 2-hydroxyethanoic acid (glycolic acid) by N-bromosaccharin leads to the formation of the corresponding aldehydes. Oxidation kinetics has been studied in aqueous acetic acid in the presence of Hg(II) acetate and cationic surfactant (CTAB). The reaction shows first order dependence in oxidant while Michaelis Menten type of kinetics has been observed with respect to reductant. The oxidation is inhibited by CTAB. Variation in [H+] shows complex kinetics. Addition of reaction product, saccharin, retards the rate of reaction. Effect of variation of dielectric constant of the medium, ionic strength of the medium and concentration of Hg(II) acetate have also been investigated. Activation parameters have been computed. The observed results are explained by Piszkiewicz model, which concludes that reaction occurs in the aqueous acetic acid phase.